Bone Health and Bone-targeted Therapies for Prostate Cancer: a Programme in Evidence-based Care — Cancer Care Ontario Clinical Practice Guideline. Issue 6 (June 2017) - Alibhai, S.M.H.; Zukotynski, K.; Walker-Dilks, C.; Emmenegger, U.; Finelli, A.; Morgan, S.C.; Hotte, S.J.; Winquist, E.
Abstract: Aims: To make recommendations with respect to bone health and bone-targeted therapies in men with prostate cancer. Materials and methods: A systematic review was carried out by searching MEDLINE, EMBASE and the Cochrane Library from inception to January 2016. Systematic reviews and randomised-controlled trials were considered for inclusion if they involved therapies directed at improving bone health or outcomes such as skeletal-related events, pain and quality of life in patients with prostate cancer either with or without metastases to bone. Therapies included medications, supplements or lifestyle modifications alone or in combination and were compared with placebo, no treatment or other agents. Disease-targeted agents such as androgen receptor-targeted and chemotherapeutic agents were excluded. Recommendations were reviewed by internal and external review groups. Results: In men with prostate cancer receiving androgen deprivation therapy, baseline bone mineral density testing is encouraged. Denosumab should be considered for reducing the risk of fracture in men on androgen deprivation therapy with an increased fracture risk. Bisphosphonates were effective in improving bone mineral density, but the effect on fracture was inconclusive. No medication is recommended to prevent the development of first bone metastasis. Denosumab and zoledronic acid are recommended for preventing or delaying skeletal-related events in men with metastatic castration-resistant prostate cancer. Radium-223 is recommended for reducing symptomatic skeletal events and prolonging survival in men with symptomatic metastatic castration-resistant prostate cancer. Conclusions: The recommendations represent a current standard of care that is feasible to implement, with outcomes valued by clinicians and patients.